2006
DOI: 10.1103/physrevb.73.064407
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced abrupt change in magnetization of the manganite compounds(LaR)0.45(CaSr)0.55

Abstract: The ABO 3 type manganites ͑LaR͒ 0.45 ͑CaSr͒ 0.55 MnO 3 ͑R=Eu 3+ -a nonmagnetic ion and Tb 3+ -a magnetic ion͒ which possess large A-site size-disorder, exhibit metamagnetic transitions as a function of magnetic field. Below a certain crossover temperature and depending on the magnetic field sweep rate, the metamagnetic transition transforms from a broad to sharp step-like transitions. This crossover temperature increases on increasing the field sweep rate. The effect of field sweep rate on the critical field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…It has been reported that many manganites show multiple steps with reduction in temperature. [14][15][16][17][26][27][28] The M-H curves were also recorded without thermal cycling. Figure 5 shows the two loop magnetization isotherms for Ce͑Fe 0.975 Ga 0.025 ͒ 2 without thermal cycling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that many manganites show multiple steps with reduction in temperature. [14][15][16][17][26][27][28] The M-H curves were also recorded without thermal cycling. Figure 5 shows the two loop magnetization isotherms for Ce͑Fe 0.975 Ga 0.025 ͒ 2 without thermal cycling.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the AFM-FM transition, it has been found that the breakdown of charge and orbital ordering also leads to the magnetization jumps in the case of manganites, in general. 15,17 Martensitic accommodation of strain associated with the AFM-FM transition is found to affect the magnetization behavior. 11 Detailed studies have been performed on various manganites using the field sweep rate and time dependence of magnetization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was first observed by Hebert et al 7 when the Mn sub-lattice was diluted with some magnetic or non-magnetic impurities and subsequently by Fisher et al 8 by augmenting the cation-disorder at the Asite 11 . Such low temperature metamagnetic behavior in manganite compounds is remarkable as these first order transitions display a crossover from a smooth to a sharp metamagnetic transition [7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…20 Also, much sharper stair-case like metamagnetic transitions were seen in several other Pr and Nd based bulk manganites. 21,22 The possible reason 21 for the current broadened transition could be that the spins are strongly coupled to the lattice, hindering the kinetics of AFM to FM phase transitions. The sharpness of this transition also depends upon the field sweep rate and disorder present in the compound, and is the subject of future work.…”
Section: B Pulse Field Magnetic Propertiesmentioning
confidence: 99%